The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1186/s12912-016-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration error reporting and associated factors among nurses working at the University of Gondar referral hospital, Northwest Ethiopia, 2015

Abstract: BackgroundMedication administration is the final step/phase of medication process in which its error directly affects the patient health. Due to the central role of nurses in medication administration, whether they are the source of an error, a contributor, or an observer they have the professional, legal and ethical responsibility to recognize and report. The aim of this study was to assess the prevalence of medication administration error reporting and associated factors among nurses working at The Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 26 publications
(36 reference statements)
2
53
2
4
Order By: Relevance
“…The finding of this study was similar to a study done in two southern Ethiopia hospitals (58.5%) [11]. However, it was much lower than a study conducted in France (72.6%) [27]. The difference likely to be due to the difference in the study setting (the previous study was conducted in a specified ward, while this study was conducted in all clinical departments of three hospitals).…”
Section: Discussionsupporting
confidence: 81%
“…The finding of this study was similar to a study done in two southern Ethiopia hospitals (58.5%) [11]. However, it was much lower than a study conducted in France (72.6%) [27]. The difference likely to be due to the difference in the study setting (the previous study was conducted in a specified ward, while this study was conducted in all clinical departments of three hospitals).…”
Section: Discussionsupporting
confidence: 81%
“…[5,[11][12][13][15][16][17][18][19] The second error was the wrong dosage or wrong dosage calculation which was reported by 7 articles. [5,9,11,15,[20][21][22] Other types of errors identified were incorrect medication, [9,[20][21][22]incorrect route, [12,15,18,21]incorrect patient, [5,12,21,22]error in technique, [16,18,23] omitting a drug due to drug availability [17,18] and administration of a drug which is not prescribed. [13,15]There was another type of error that was less apparent which is documentation.…”
Section: Types Of Medication Administration Errorsmentioning
confidence: 99%
“…In this review, fear of negative consequences such us punishment and losing a job after self-reporting [9,11,[32][33][34]12,13,25,26,[28][29][30][31]and fear of blames [13,22,30,33] were reported to be barriers to self-reporting.…”
Section: Self-reporting Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that the country should establish the medication errors reporting system. 17 Thus, to prevent medication administration errors there should be a way for reporting them within the hospital but still there are some barriers that hinder this activity like lack of precise definition, no effort in reporting, fear, and administrative responses. 18,19 Rwanda was among 16 countries where they found that it had not a clear reporting system of medication errors.…”
Section: Introductionmentioning
confidence: 99%